Between doctors and healers: managing meanings and practices of the health-disease-care process in an Argentine Catholic charismatic movement - Ana Lucía Olmos Álvarez (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2018)
This work describes and analyzes the trajectories and strategies in the search for healing among participants of a charismatic Catholic healing movement in Argentina. Using ethnographic research carried out between July 2009 and April 2015, the article focuses on conceptions, practices and experiences surrounding health-disease-care processes. It is highlighted that disease management requires both a cognitive and a practical response, in this case involving two primary therapeutic resources: biomedicine and religious therapies. It is also postulated that each resource is sought at specific moments in the trajectories and the passage from one to another implies a change from a restricted to a holistic notion of the health-disease-care process.